2008
DOI: 10.1590/s0100-204x2008000600013
|View full text |Cite
|
Sign up to set email alerts
|

Time-related action of Lactobacillus plantarum in the bacterial microbiota of shrimp digestive tract and its action as immunostimulant

Abstract: -The objective of this work was to assess the time-related action of probiotic Lactobacillus plantarum in the bacterial microbiota of the digestive tract of Litopenaeus vannamei, and the relation of total haemocyte count and serum phenol oxidase activity of shrimp challenged with Vibrio harveyi. Shrimps were fed with a probiotic-supplemented diet, for eight days, then shifted to a commercial diet. Shrimps fed only with the commercial diet served as control. Evaluations were made on the 8 th day of experiment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 32 publications
8
33
1
7
Order By: Relevance
“…As observed by Vieira et al (2008) in laboratory conditions, the present study demonstrated that the diets supplemented with L. plantarum also altered the microbiota of shrimp on farm. The presence of lactic acid bacteria in the intestinal tract can enhance the animal immune system, resulting in shrimp more resistant to disease in the cultivation environment.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…As observed by Vieira et al (2008) in laboratory conditions, the present study demonstrated that the diets supplemented with L. plantarum also altered the microbiota of shrimp on farm. The presence of lactic acid bacteria in the intestinal tract can enhance the animal immune system, resulting in shrimp more resistant to disease in the cultivation environment.…”
Section: Resultssupporting
confidence: 84%
“…In L. vannamei, the use of a diet supplemented with L. plantarum stimulated an immunological response as reported by Vieira et al (2008Vieira et al ( , 2010. However, we observed no differences in immunological parameters between treatments (P≥0.05) ( Table 4).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Nevertheless, several studies have demonstrated that such bacterial microbiota can be modified by the addition of Gram-positive bacteria in the diet (Ziaei-Nejad et al, 2006;Vieira et al, 2008) or in the culture water (Rengpipat et al 1998;. Accordingly, in the present study, shrimp fed L. plantarum supplemented diet showed less viable total and vibrio bacteria, and high amounts of lactic bacteria.…”
Section: Resultssupporting
confidence: 42%